PENGARUH EMPLOYEE ENGAGEMENT, SELF-ESTEEM, DAN SELF-EFFICACY TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI PADA PT. AGUNG TOYOTA KOTA BENGKULU - Webby Irma Suryani; Janusi Waliamin; Sintia Safrianti (MANAJEMEN, 2025)
This research investigates the impact of employee engagement, self-esteem, and self-efficacy on job performance, with organizational culture acting as a moderating factor at PT. Agung Toyota in Bengkulu City. Utilizing a quantitative explanatory methodology, the study adopts PLS-SEMi(Partial Least Squares Structural Equation Modeling)I and MRA (Moderated Regression Analysis), with participation from 120 permanent employees. Data was obtained via online surveys and processed using the SmartPLS 4 software. Findings reveal that both self-esteem and organizational culture exert a significant effect on job performance. In contrast, employee engagement and self-efficacy show no notable influence on performance outcomes. Additionally, organizational culture does not significantly moderate the relationship between the three independent variables and performance, highlighting its limited moderating function. The research offers theoretical contributions to human resource development and provides practical suggestions for enhancing employee productivity by reinforcing individual psychological factors and cultivating a supportive workenvironment.